The Effect of Organizational Commitment and Organizational Culture on Employee Performance Through Employee Job Satisfaction as An Intervening Variable (Study on BPJS Employment in the Greater Aceh Region) - Kurniadi; Kiki Farida Ferine (Yayasan Multidimensi Kreatif, 2024)
This study was conducted to determine the influence of organizational commitment and organizational culture on employee performance through employee job satisfaction as an intervening variable. With the type of quantitative research used, the primary data source used to collect data by distributing questionnaires, populsion of 107 employees and a sample of 107 employees and the saturated sample technique used, the model of this research is a phat analysis, the results of this study are as follows: Organizational Culture has a positive and significant effect on Job Satisfaction with a sample size of 0.687 and p values of 0.000. Organizational Culture had a positive and significant effect on Performance with the original sample value of 0.370 and p values of 0.003. Job Satisfaction had a positive and significant effect on Performance with the original sample value of 0.338 and p values of 0.002. Organizational Commitment had a positive and significant effect on Job Satisfaction with the original sample value of 0.237 and P values of 0.001. Organizational commitment had a positive and significant effect on the performance with the original sample value of 0.198 and P values of 0.014. Organizational Culture has a positive and significant indirect effect on Performance through Job Satisfaction with the original sample value of 0.232 and P values of 0.002. Organizational Commitment has a positive and significant indirect effect on Performance through Job Satisfaction with an original sample value of 0.800 and P values of 0.014.